High sensitive trypsin activity evaluation applying a nanostructured QCM-sensor - Stoytcheva, M.; Zlatev, R.; Cosnier, S.; Arredondo, M.; Valdez, B. (Biosensors & bioelectronics, 2013)
The medical diagnostic, the industry, and the biotechnology require rapid, sensitive, and easy to use methods for trypsin activity determination. A simple approach, which meets all these requirements, based on Quartz Crystal Microbalance (QCM) was developed, analytically characterized and described in the present work. QCM application allows rapid trypsin activity evaluation by real time monitoring of the enzymatic degradation of the substrate. The new approach suggested in this work takes advantage of nanoparticles loaded gelatin employment as a trypsin substrate, deposited on the QCM crystal. The heavy nanoparticles leave the substrate layer together with the products of its enzymatic degradation provoking thus a greater decrease of the total QCM crystal mass compared with the non charged substrate. As a result, a higher sensor frequency response occurs. A 10 fold improvement of the LOD was achieved for trypsin activity evaluation applying the proposed method with Ag nanoparticles loaded gelatin (7.5×10−4UmL−1 vs. 7.5×10−3UmL−1 obtained by the “classic” QCM method). The approach subject of this work can be applied with any substrate degrading enzyme. ► High sensitive trypsin activity evaluation method was proposed applying a QCM-sensor. ► Signal amplification was reached using nanoparticles loaded substrate. ► 10-fold LOD improvement was achieved compared with the “classic” QCM method. ► This powerful approach could be applied with any substrate degrading enzyme.